2019
DOI: 10.15587/1729-4061.2019.179382
|View full text |Cite
|
Sign up to set email alerts
|

Development of the aeromagnetic space debris deorbiting system

Abstract: Розглянуто можливість створення аеромагнітної системи відведення об'єктів космічного сміття з низьких навколоземних орбіт. Особливістю конструкції даної аеромагнітної системи відведення є застосування магнітних органів керування відносним положенням аеродинамічного елементу з використанням постійних поворотних магнітів, що екрануються за допомогою спеціальних капсул екранів зі створами. Слід зазначити, що ця система пропонується для аеродинамічно нестійких космічних апаратів. Також, для аналізу працездатності … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Taking these shortcomings into account, a new design scheme of an aeromagnetic deorbiting system with executive devices based on permanent magnets was proposed in [4]. This system was proposed for deorbiting worked-out spacecraft from low Earth orbits as a part of the solution to the global problem of choking of the near-Earth space.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 4 more Smart Citations
“…Taking these shortcomings into account, a new design scheme of an aeromagnetic deorbiting system with executive devices based on permanent magnets was proposed in [4]. This system was proposed for deorbiting worked-out spacecraft from low Earth orbits as a part of the solution to the global problem of choking of the near-Earth space.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…This system was proposed for deorbiting worked-out spacecraft from low Earth orbits as a part of the solution to the global problem of choking of the near-Earth space. The results of studies using a nonlinear discrete controller in [4] have shown its performance and advantages compared to the electromagnetic systems. However, no complete analysis and synthesis of the law of angular motion control were provided.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations